Caracterização bioquímica e funcional de uma Fosfolipase A2 isolada da peçonha de Bothrops alternatus - Paschoal, Tamires dos Santos (2015)
The phospholipases A2 (PLA2s) are part of a superfamily of proteins with similar enzymatic functions, responsible for the hydrolysis of phospholipids and, thus, for the release of fatty acids and lysophospholipids which play a role in various physiological activities, like inflammation, platelet activation, signaling, cell proliferation and migration. The present study aimed at the functional and biochemical characterization of an acidic phospholipase A2 isolated from the Bothrops alternatus snake venom, named BaG2P5. BaG2P5 was purified using three chromatographic steps: ion exchange on DEAE-Sephacel, molecular exclusion in Sephadex-G75 and hydrophobic interactions in Phenyl-Sepharose. The mass spectrometry was used to determine the purity and the molecular mass of BaG2P5, which was approximately 14 kDa. The protein showed a potent time and dose-dependent phospholipasic activity, evaluated by indirect hemolysis method, and was able to cause muscle tissue damage and leukocyte recruitment when intramuscularly administered. In addition, BaG2P5 presented in vitro toxicity against HeLa cells, and inhibited platelet aggregation induced by epinephrine in a time and dose dependent manner. On the other hand, BaG2P5 could not induce intraplantar edema and hyperalgesia in rat paws. These results contribute for studies on snake venom composition and for better understanding of the role of phospholipases in snake envenoming. Furthermore, the characterization of toxins with anti-platelet and anti-cancer properties is an important step in the discovery of new molecules with therapeutic potential.